Brazing of (TiB + Y2O3) reinforced titanium matrix composites using CuTiZrNi amorphous filler alloy. (April 2020) - Zhu, Dongdong; Xu, Haitao; Dong, Duo; He, Yanming; Wang, Xiaohong; He, Qing
Abstract: (TiB + Y2 O3 )/titanium matrix composites (TMCs) were brazed with CuTiZrNi amorphous filler alloy. The joint showed integral interfaces without any imperfections. The joint brazed at 900 °C can be divided into 2 zones. Microstructure of zone I was demonstrated as (Ti, Zr)2 (Cu, Ni) + α-Ti + TiB and zone II was a continuous TiCu reaction layer. Higher temperature accelerated the elemental diffusion between the joint and substrates, thickened the brazing seam and TiCu layer diminished when brazed at 980 °C. The amount and size of (Ti, Zr)2 (Cu, Ni) phase decreased while the amount of TiB and Y2 O3 phase increased with increasing brazing temperature. When brazing temperature rose higher than 980 °C, the joint was occupied by reticulation-distributed (Ti, Zr)2 (Cu, Ni) + α-Ti eutectic structure. At higher brazing temperatures, TiB was greatly refined as the decomposition of the original TiB enhanced and more reconstructed TiB precipitated during cooling. The joint shear strength increased greatly with increasing brazing temperatures and reached the maximum of 646.0 MPa when brazed at 1020 °C. Further increasing the brazing temperature to 1060 °C, the joint strength did not change obviously. The fracture locations changed when brazed at different temperatures. The joints at different parameters showed cleavage fracture or quasi-cleavage fracture. Highlights: An innovative CuTiZrNi amorphous filler alloy was used to braze TMCs. The maximum joint shear strength of 646 MPa was obtained. Evolution of microstructure and mechanical properties of the joints were studied.